DATA MINING FOR SOFTWARE ENGINEERING. - Xie, Tao; Thummalapenta, Suresh; Lo, David; Liu, Chao (Computer (00189162), 2009)
The article focuses on the increasing application of data mining algorithms by computer software engineers and discusses algorithms for effective mining. The aim of software engineers is to improve software productivity and quality. The challenges of mining software engineering (SE) data are examined. The categories of SE data include sequences, graphs and text.